Laser induced graphene enhancing polyvinylidene fluoride (PVDF) films for advanced applications - Vala Can Aşkan; Bahar Şölen Akdemir; Nihan Aydemir; Ahmet Yavuz Oral (Materials Research Express)
Polymers are emerging as cornerstone materials for electronic applications due to their unparalleled combination of affordability, chemical stability, and ease of fabrication. Among them, polyvinylidene fluoride (PVDF) stands out as a promising candidate whose properties can be further improved by incorporating functional fillers. In this study, the potential use of laser-induced graphene (LIG) as a filler to improve the electrical properties of PVDF films is investigated. LIG was incorporated into PVDF films in the liquid precursor, and the coating was carried out using a drop-casting technique that allowed controlled variations in LIG concentration. The results show that increasing the LIG content dramatically increases the electrical conductivity of PVDF films and leads to remarkable changes in the microstructure. These results show that LIG is a highly effective filler for PVDF, paving the way for advanced applications in flexible sensors, energy storage systems, and wearable devices. Future research should focus on optimizing LIG concentration and distribution to maximize the performance of PVDF-based composites.